O necessário equilíbrio entre a proteção de dados pessoais e a atuação estatal na persecução penal: análise do anteprojeto NEFI 2020, limites e possibilidades, a compreensão da proteção integral dos direitos fundamentais, especialmente da segurança pública e da privacidade, à luz do paradigma do Estado Democrático de Direito - Oliveira, Luciano Rocha de (2022)
In a scenario of significant technological advances with repercussions on the use of personal data for public security, this research asked: the protection of personal data in the criminal field is constitutionally adequate to the integral protection of fundamental rights, especially in the scope of public security and privacy, in the light of the paradigm of the Democratic State of Law? It was established, as a general objective, to understand the proposal of the Draft Draft of the General Law for the Protection of Criminal Data (Preliminary Draft Nefi) and its reflexes in the investigative activity of the State, trying to identify a balance between this activity and the protection of privacy in the light of the State. Democratic of Law. In terms of specific objectives, we sought to identify how the idea of personal data protection came about in the world and, more specifically, in Brazil. Still, an attempt was made regarding the emergence of the General Data Protection Law in Brazil, its reason for being, its essential concepts, and its non-applicability in the scope of public security and criminal prosecution. The adequacy and possible balance between privacy and public security were analyzed, as well as the Draft of the General Law for the Protection of Criminal Data, describing its content, normative reference, and principles. The reflexes of this Preliminary Project in the scope of public security were investigated, and its main criticisms were presented. The starting point was the initial hypothesis that personal data deserve protection and are part of fundamental rights. Still, protection cannot weaken state action in its protective function of society. As a theoretical framework, the work The General Theory of Digital Law by Wolfgang Hoffmann-Riem, which analyzes the digital transformation and the challenges for Law, and the work of Douglas Fischer and Frederico Valdez Pereira, which deals with procedural obligations and positive criminal penalties, according to the European and Inter-American Courts of Human Rights. The aim was to be able to point out the effects of digital transformation on society, as well as the need for a positive action on the part of the State from the bibliographic and documentary review procedure with content analysis under the hypothetical-deductive method of research, starting from the premise of the European Union model as being adequate to materialize data protection in Brazilian law